Prokrastinasi Akademik Mahasiswa Tingkat Akhir: Studi tentang Hubungan Locus of Control dan Strategi Coping: Indonesia - Enindari, Woro Nauraningrum; Nurmala , Sukma (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2023)
The purpose of this study was to determine the relationship between locus of control and coping strategies with academic procrastination of final year students. This study used a correlational quantitative approach involving 138 participants. The criteria for respondents in this study were active final year students (semester 7 and above) at universities in Indonesia and were working on a thesis. There are 3 measuring instruments used, namely The Multidimensional Locus of Control IPC Scale (2011), Academic Coping Strategy Scale (2017), and Academic Procrastination Scale (2020). The results of this study indicate a positive relationship (the direction of the relationship is directly proportional) between locus of control and academic procrastination and a negative relationship (the direction of the relationship is inversely proportional) between coping strategies and academic procrastination. Keywords: Locus of Control, Final Year Students, Academic Procrastination, Coping Strategies.